2018
DOI: 10.5194/amt-11-4073-2018
|View full text |Cite
|
Sign up to set email alerts
|

Exploring systematic offsets between aerosol products from the two MODIS sensors

Abstract: Abstract. Long-term measurements of global aerosol loading and optical properties are essential for assessing climate-related questions. Using observations of spectral reflectance and radiance, the dark-target (DT) aerosol retrieval algorithm is applied to Moderate Resolution Imaging Spectroradiometer sensors on both Terra (MODIS-T) and Aqua (MODIS-A) satellites, deriving products (known as MOD04 and MYD04, respectively) of global aerosol optical depth (AOD at 0.55 µm) over both land and ocean, and an Ångström… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(70 citation statements)
references
References 81 publications
(99 reference statements)
6
48
0
Order By: Relevance
“…For V/A and V/T, these are 35% and 32% for the daily and 56% and 53% for the gridded median offsets, respectively, somewhat lower and largely driven by differences in well‐sampled tropical and midlatitude deserts. For T/A, in most areas, Terra is slightly higher than Aqua; this was also observed by Levy et al (), looking at DT retrieval results. Levy et al () investigated the magnitudes of calibration differences and diurnal variations on the Terra‐Aqua offset and found that neither alone was responsible for it.…”
Section: Global and Regional Patternssupporting
confidence: 82%
See 1 more Smart Citation
“…For V/A and V/T, these are 35% and 32% for the daily and 56% and 53% for the gridded median offsets, respectively, somewhat lower and largely driven by differences in well‐sampled tropical and midlatitude deserts. For T/A, in most areas, Terra is slightly higher than Aqua; this was also observed by Levy et al (), looking at DT retrieval results. Levy et al () investigated the magnitudes of calibration differences and diurnal variations on the Terra‐Aqua offset and found that neither alone was responsible for it.…”
Section: Global and Regional Patternssupporting
confidence: 82%
“…For T/A, in most areas, Terra is slightly higher than Aqua; this was also observed by Levy et al (), looking at DT retrieval results. Levy et al () investigated the magnitudes of calibration differences and diurnal variations on the Terra‐Aqua offset and found that neither alone was responsible for it. DB uses some different bands and also applies 412‐ and 470‐nm band calibration degradation corrections (Sayer, Hsu, Bettenhausen, Jeong, & Meister, ) which DT does not.…”
Section: Global and Regional Patternssupporting
confidence: 82%
“…In this study, we derive daily over‐ocean DOD from the Aqua/MODIS Collection 6 (C6) product (Levy et al, , ) at 1°×1° resolution, following a method first developed by Kaufman et al () and then modified by Yu et al (). Briefly, this method partitions AOD into three components: dust, marine aerosol, and combustion (or pollution) aerosol.…”
Section: Data and Approachesmentioning
confidence: 99%
“…Considering the differences in potential calibration, mission lifespan, and transit time of the Terra and Aqua sensors [50], we trained two sets of models with the same aforementioned variables for both sensors in parallel, and the same training and testing data were employed to deal with each regression model for both datasets, respectively; this allowed for the comparability of the performances of the different models. All of the parameters mentioned in Section 2.1 were used.…”
Section: Model Developmentmentioning
confidence: 99%